2020
DOI: 10.1186/s13229-019-0289-x
|View full text |Cite
|
Sign up to set email alerts
|

Revised scored Sensory Perception Quotient reveals sensory hypersensitivity in women with autism

Abstract: Background: Previous research using the Sensory Perception Quotient (SPQ) has reported greater sensory hypersensitivity in people with autism spectrum condition (ASC) compared to controls, consistent with other research. However, current scoring of the SPQ does not differentiate between hyper and hyposensitivity, making it uncertain whether individuals with ASC might also show differences in hyposensitivity. Furthermore, no research to date has focused on sensory differences in females, and whether differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
4
23
2
1
Order By: Relevance
“…Males showed higher levels on the Communication and Repetitive Behaviours subscales which are therefore the likely drivers of the total-scale sex difference. Conversely, Sensory Sensitivity was found to be higher for female participants, and follows reports of higher scores on the Sensory Perception Quotient for females relative to males [ 51 ]. To our knowledge, this is the first time that a broad measure of autistic traits has shown variations in sex differences across multiple subscales, and further establishes the CATI as a psychometric measure that is relatively sensitive to the subtler differences in autistic trait presentation between males and females compared to existing scales.…”
Section: Study 2: Cati Factor Structure Verificationsupporting
confidence: 70%
See 1 more Smart Citation
“…Males showed higher levels on the Communication and Repetitive Behaviours subscales which are therefore the likely drivers of the total-scale sex difference. Conversely, Sensory Sensitivity was found to be higher for female participants, and follows reports of higher scores on the Sensory Perception Quotient for females relative to males [ 51 ]. To our knowledge, this is the first time that a broad measure of autistic traits has shown variations in sex differences across multiple subscales, and further establishes the CATI as a psychometric measure that is relatively sensitive to the subtler differences in autistic trait presentation between males and females compared to existing scales.…”
Section: Study 2: Cati Factor Structure Verificationsupporting
confidence: 70%
“…This pattern was supported by data from the Dutch translation of the scale, where a moderate positive correlation was reported between the total scores of the hyper- and hypo-sensitivity items [ 54 ]. Furthermore, significantly higher levels of hyper-responsiveness in autistic compared to non-autistic women have been reported using a revised version of the Sensory Perception Quotient, but no differences in hypo-sensitivity were reported [ 51 ]. Consequently, in the interest of brevity the development of the current version of the CATI was restricted to items relating to hyper-responsiveness to sensory stimuli.…”
Section: Study 3: Convergent Validity For Cati Subscalesmentioning
confidence: 99%
“…Previous research into sensory sensitivity in autism has been mixed when considering sex differences [9,57]. Recent studies on the SPQ, both on data within the Netherlands Autism Register (of which this dataset is a subsample) and outside, found that autistic females had higher sensory sensitivity than both autistic males [42] and non-autistic females [43]. Research within the general population also suggests that females may be more sensitive than males across a range of modalities [34,58], with hormones thought to play a key role [59].…”
Section: Discussionmentioning
confidence: 99%
“…The 35 item Sensory Perception Quotient (SPQ) was developed to assess sensory sensitivity in adults with and without autism, and shows good internal consistency and validity [9,42,43]. It is assessed on a four-point Likert scale across ve sensory modalities.…”
Section: Sensory Sensitivitymentioning
confidence: 99%
“…Therefore, whilst CSS studies have acknowledged that general sensory sensitivity, and not just pain, is part of central sensitisation [ 17 21 ], the mechanisms of individual differences in sensory sensitivity within this population, as well as the neurodivergent and general population, are still unclear [ 22 ]. Studies on sensory differences in autism are plentiful [ 13 , 15 , 23 , 24 ] but research specifically on the autistic pain experience is more limited. Research on acute pain in autism, and quantitative sensory testing studies, has suggested that autistic people have a normal or hypersensitive physiological response to acute pain, but may express pain differently [ 25 28 ] and also experience more pain-related anxiety [ 29 ], but it has not yet been established whether this anxiety contributes to, or is caused by, altered pain sensitivity.…”
Section: Introductionmentioning
confidence: 99%